Evaluation of a Three-dimensional printable and two CAD/CAM hybrid resin materials used as permanent single tooth restoration: An in-Vitro study - Noha Saadoun; Mohamed Sherif Mohamed Salah Farag; Rania El-Saady Badawy (BMC Oral Health)
Abstract Objectives To evaluate and compare three commercially available hybrid resin materials used for additive and subtractive production (CAD/CAM applications) of permanent single-tooth restorations. Materials and methods One-hundred and twenty-five bar-shaped specimens (14 mm length, 2 mm width, and 2 mm thickness) of 3 different hybrid resin materials were used in this study, being classified into 5 groups (n = 25). Group I: Lava Ultimate, group II: Vita Enamic, group III: Flexcera Smile Ultra+ A, group IV: Flexcera Smile Ultra+ B and group V: Flexcera Smile Ultra+ C. Lava Ultimate and Vita Enamic specimens were prepared with a low-speed water-cooled diamond microsaw. A digital light processing 3D printer was utilized to print Flexcera Smile Ultra+ specimens of 3 different printing angles (0, 45, 90 angles). Specimens were investigated regarding degree of conversion (DC), surface roughness, flexural strength (FS) & modulus (FM) and fractographic analysis. The collected data was tabulated and subjected to statistical analysis. One Way ANOVA test was used to analyze data statistically. Results Flexcera Smile Ultra+ B group showed the highest statistically DC value (46.40). Vita Enamic group showed the highest statistically surface roughness value (0.360). Lava Ultimate group showed the highest statistically FS value (169.87), however Vita Enamic group showed the highest statistically FM value (13.45). Scanning electron microscope images of fractured specimens revealed a compression curl in the upper part and the fracture origin in the lower portion of the surface, which denotes specimens bending. Microcracks voids, arrest lines and hackle lines are also detected. Fractured specimens showed different crack propagation behaviors. Conclusions Different printing angles (orientations) strongly affected degree of conversion, flexural strength and modulus of the 3D printed material. FS and FM of the 3D printed material were lower than those of CAD/CAM blocks. The different groups showed variable degrees of surface roughness. The fracture surfaces of the different groups revealed common features, indicating bending and showing different crack pathways.